(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Matviychuk L. А. Fundamentals of professional knowledge of future software engineers by means of information and communication technologies. In the article the justification for the content of professional knowledge, the principles topical use of ICT in the learning process, the levels of formation of knowledge and personal qualities of future software engineers.